CDKN2A as transcriptomic marker for muscle-invasive bladder cancer risk stratification and therapy decision-making - Worst, Thomas; Weis, Cleo-Aron Thias; Erben, Philipp (Scientific reports, 2018)
Deletions of the cell cycle control gene CDKN2A are described as progression markers of non-muscle invasive bladder cancer and to be associated with fibroblast growth factor 3 (FGFR3) mutations. The prognostic role of CDKN2A RNA expression in muscle invasive bladder cancer (MIBC) is under discussion. In 80 MIBC patients (m/f 60/20) who underwent radical cystectomy the expression of CDKN2A and FGFR3 was examined with qRT-PCR (test cohort). The MDA cohort (n = 57) and the TCGA cohort (n = 365) served for validation. The expression of drug target genes and TCGA molecular subtypes was correlated with CDKN2A expression. In the test cohort CDKN2Ahigh patients (n = 8; 10.0%) had a significantly shorter recurrence-free (p = 0.018) and disease-specific (p = 0.006) survival compared to the rest of the cohort. A similar stratification was seen in the validation cohorts (CDKN2Ahigh: n = 7, 12.3%, p = 0.001; n = 46, 12.6%, p = 0.011). In the TCGA cohort these patients had a comparably low expression of drug target genes. The expression of CDKN2A significantly differed among TGCA molecular subtypes. 71.7% of CDKN2Ahigh were TCGA basal squamous tumours but also show divergent molecular features compared to this group. In summary CDKN2A RNA expression-based risk stratification of MIBC allows the identification of a CDKN2Ahigh poor prognosis group with low expression of drug target genes.